Tribal ecclesiology : a critical synthesis of early Christian traditions and cultural traditions of Northeast India - Zolawma, R. (New Delhi Christian World Imprints, 2016)
Study conducted in Mizoram, India.
Originally presented as the author's thesis (Doctor of Theology--Serampore College (University)) under the title: Towards a tribal ecclesiology through a critical synthesis of select early Christian traditions and tribal cultural traditions of Northeast India, specially Mizoram.
Includes bibliographical references (pages 279-306).
Keywords: Lushai (Asian people) -- India -- Mizoram -- Religion; Christianity and culture -- India -- Mizoram; Mizoram (India) -- Church history; Mizoram (India) -- Religious life and customs